Pengembangan multimedia interaktif terintegrasi dengan LKS pada pokok bahasan pesawat sederhana - Ade Suseno; Riswanto Riswanto; Partono Partono (UNIVERSITAS INDRAPRASTA PGRI, 2019)
The pre-survey result of the problem school that media that used in school have not assisted student learning, and some teachers use an interactive multimedia..The purpose of this research is to produce an integrated interactive multimedia development with student worksheet on simple machine subject by using powerpoint. The type of this research is Reseach and Development. The model development that used is the ADDIE development model includes 5 step: Analysis, Design, Development, Implementation, and Evaluation. The feasibility of the result product could be reviewed in 3 aspects: software engineering aspects, visual communication aspect and learning design aspects.The results that the powerpoint have fulfill the criteria that showed by validation with a very feasible and good criteria. The product assessment by media expert reached 89.1% and material experts reached 89.0%. Furthermore, the product assessment by teacher response reaches 90.5% and product assessment by Student response reaches 87.1%